Effect of Silicon on Growth and Productivity of Sesamum indicum L. (Ubon Ratchathani 3) under Salinity Stress - Srikan, Nuengruethai; Chutimanukul, Preuk (Thai Journal of Science and Technology, 2023)
The aim of this study was to research the effect of silicon on growth and yield of black sesame (Ubon Ratchathani 3) under salinity conditions. The experimental design was 4x4 Factorial in completely randomized design (CRD) with 5 replications. Factor A consisted of 4 levels of the concentration of sodium chloride (NaCl) (0, 20, 40 and 60 mmol/L) and factor B included 4 levels of silicon in the form of silicic acid (Si(OH)4) (0, 30, 60 and 90 kg/rai). The results found that leaf width showed the most effective performance in sodium chloride 0 mmol/l with silicon 0 kg/rai. Height, leaf length, stem dry weight, pods dry weight, leaf dry weight showed the most effective performance in sodium chloride 0 mmol/l with silicon 90 kg/rai. Number of leaf showed the most effective performance in sodium chloride 0 mmol/l with silicon 60 kg/rai. Root length, number of pods, yield per plant, yield per rai, 1000-weight showed the most effective performance in sodium chloride 20 mmol/l with silicon 90 kg/rai. Root dry weight and photosynthetic rate showed the most effective performance in sodium chloride 40 mmol/l with silicon 90 kg/rai.